Nonoperative Management of Leaks After Laparoscopic Sleeve Gastrectomy With Endoscopic Stents in a Tertiary Referral Center - Fırat, Özgür; Demir, Halit Batuhan; Sezer, Taylan Özgür; Bozkaya, Halil; Özütemiz, Ömer; Ersin, Sinan (Turkish Journal of Gastroenterology, 2022)
Background: Laparoscopic sleeve gastrectomy (LSG) is a frequently performed operation. Leaks are formidable complications; however, the optimal management of these leaks is controversial. Methods: We retrospectively reviewed the medical records of 15 patients referred to our tertiary center between 2012 and 2016 with leaks after LSG. Results: In 12 patients with whom ongoing leaks were identified, stents were inserted with the intent of definitive therapy. In addition to attempts at source control, percutaneous drainage was carried out for intraabdominal collection in 9 patients and pleural effusion in 4 patients. The length of stay in the intensive care unit was significantly shorter in patients referred earlier or in those without any intervention. Conclusion: LSG leaks can be treated nonoperatively in well-organized centers under meticulously designed protocols, depending on the clinical condition of the patient.